2022
DOI: 10.3389/fnins.2022.1084118
|View full text |Cite
|
Sign up to set email alerts
|

Application of artificial intelligence models for detecting the pterygium that requires surgical treatment based on anterior segment images

Abstract: Background and aimA pterygium is a common ocular surface disease, which not only affects facial appearance but can also grow into the tissue layer, causing astigmatism and vision loss. In this study, an artificial intelligence model was developed for detecting the pterygium that requires surgical treatment. The model was designed using ensemble deep learning (DL).MethodsA total of 172 anterior segment images of pterygia were obtained from the Jiangxi Provincial People’s Hospital (China) between 2017 and 2022. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…[ 43 , 44 ]. GLSZM, GLRLM, and GLCM are regional textural features and have been applied to emphasize local heterogeneity information, as the ability to distinguish patients with distinct prognoses has already been confirmed for other tumors [ 45 47 ]. A previous study demonstrated that heterogeneity in MRI distribution within tumors serves as a valuable biomarker for predicting treatment outcomes in patients with NPC [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 43 , 44 ]. GLSZM, GLRLM, and GLCM are regional textural features and have been applied to emphasize local heterogeneity information, as the ability to distinguish patients with distinct prognoses has already been confirmed for other tumors [ 45 47 ]. A previous study demonstrated that heterogeneity in MRI distribution within tumors serves as a valuable biomarker for predicting treatment outcomes in patients with NPC [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these investigations use models like ResNet50, AlexNet, LSTM, and Inception, which have also been applied to pterygium. Common models include VGG16 [4], [7], [20], [21], ResNet, in some of its variants such as ResNet18, ResNet50, or ResNet101, [4], [20], [21], AlexNet and GoogleNet [4], [20]. Other architectures not as common but also relevant include DenseNet201 [4], the EfficientNet family [22] and the MobileNet family.…”
Section: Related Workmentioning
confidence: 99%
“…Table 2 [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] shows a summary of 16 papers that used deep learning methods to assist in diagnosing pterygium in chronological order, along with their summary information. Different from conventional methods, the researchers first tried on the pterygium classification task due to the end-toend characteristics of deep learning.…”
Section: S U M M a Ry O F D E E P L E A R N I N G M E T H O D S Appli...mentioning
confidence: 99%